Akselerasi Sertifikasi Halal Self-Declare melalui Pendampingan Partisipatif Berbasis Digital bagi UMKM di Desa Langkap - Muhammad Imamul Muttaqin Arisandi; Bustomi Arisandi; Bahrul Ulum; Zainal Hakim; Jamaluddin Akbar (Journal of Community Service and Engagement, 2026)
This Community Service Program is motivated by the low rate of halal certification among Micro, Small, and Medium Enterprises (MSMEs) in Langkap Village, Burneh District, Bangkalan, despite the government's mandatory halal regulations. The primary problems faced by partners include limited digital literacy, complex administrative procedures, and the misconception that certification costs are expensive. The objective of this activity is to accelerate Sharia compliance and business legality through the self-declaration mechanism. The method employed in this service is Participatory Action Research (PAR), which combines policy socialization stages, technical training on the halal information system operations, and participatory self-audit mentoring. The results show a significant increase in partner capacity, with the digital system operation understanding score soaring by 283.3%. Furthermore, this activity successfully facilitated the issuance of 25 Business Identification Numbers (Nomor Induk Berusaha) and 22 official halal certificates for local culinary products, while 3 others are currently in the final verification process. This program proves that intensive technical mentoring is capable of dismantling administrative barriers and strengthening the Sharia economic ecosystem at the rural level sustainably.